Initial experience of endovascular aneurysm repair at the Dr. Eduardo Liceaga General Hospital of Mexico - Sierra-Juárez, Miguel A.; Valderrama-Treviño, Alan I.; González-Martínez, Itaty C.; Mendoza-Barrera, German E.; Ramos-Peralta, Mariely I. (International Surgery Journal, 2024)
Background: Abdominal aortic aneurysm (AAA) is the permanent and irreversible dilation of the lower part of the aorta where the vessel expands, making it susceptible to rupture, which represents a high mortality incident. Methods: A review of clinical records was carried out from September 2021 to March 2023, patients who were diagnosed with aortic aneurysm were included in whom endovascular exclusion of abdominal and thoracic aortic aneurysm was performed at the General Hospital of Mexico by the angiology vascular and endovascular surgery department. Results: 18 endovascular repairs of aortic aneurysms were performed, of which 15.4% were female (n=6) and 84.6% male (n=12). The average proximal neck diameter in the thoracic aorta was 31 mm, average proximal neck diameter in infrarenal AAA 22.2 mm, average aneurysmal diameter in infrarenal segment 63.8 mm, thoracic 31 mm. Regarding the type of endovascular procedure, 11.1% were repaired with the fenestrated endovascular aneurysm repair (FEVAR) technique, and the same proportion with chimney endovascular aneurysm repair (ChEVAR), for a resolution with conventional EVAR of 77.7%. Complications occurred in 3 patients, 2 of which resulted in type 1a and 1b endoleaks that were reoperated and repaired with a proximal cuff, balloon angioplasty, and embolization of the aneurysmal sac with coils. Conclusions: Aortic aneurysm remains a major cause of death in adults because of aortic rupture despite advances over the past two decades that have been made in the endovascular management of large, symptomatic, and ruptured. Timely treatment is essential to prevent rupture and poor patient outcomes.